Surgical Treatment Tactics for Spontaneous Pnevmotoraxe (Eurasian Medical Research Periodical, 2023)
Treatment results of 102 patients with spontaneous pneumothorax are presented. The cause of CP in 68 (66.6%) was bullous emphysema of the lungs, in 10 (9.8%) - rupture of the postpneumonic cyst, in 7 (6.9%) - breakthrough of the echinococcal cyst into the pleural cavity, and in 17 (16.7%) - by unknown circumstances. Pleural puncture was performed in 12 patients with apical and 5 patients with moderate pneumothorax. Active drainage of the pleural cavity was performed in 12 patients with medium pneumothorax. Video-assisted thoracoscopic surgeries (VTS) were performed in 58 (56.9%) SP patients. Video-assisted atypical lung resection and pleurectomy through miniaccess was performed in 8 (13,8%) cases. It was found out that pleural cavity drainage in CP remains the main tactical method of treatment. The surgery of choice is VTS elimination of the cause of CP and obligatory pleurodesis.